Risk assessment for epidemic spread of the quarantined potato pathogen Synchytrium endobioticum in the Republic of Georgia - Andersen, K.F.; Fulton, J.; Xing, Y.; Andrade-Piedra, J.L.; Buddenhagen, C.; Forbes, G.A.; Gatto, M.; Mdivani, R.; Garrett, K.A. (2018)
Synchytrium endobioticum (causal agent of potato wart) is a devastating soilborne pathogen. Eradication is difficult and infestation can result in 100% yield loss, making this a strictly quarantined pathogen worldwide. Emerging epidemics pose a high risk to production in Georgia where potato is an essential staple, grown primarily by smallholder farmers, and yields are among the world’s lowest. S. endobioticum was first reported in Georgia in 2014 in a localized outbreak in Adjara. Because pathogen dissemination is primarily via human transport of infested tubers, understanding the local potato seed system is critical. This study was the first to systematically characterize the actors involved in seed and ware potato production and trade in Georgia. To collect this information, an expert elicitation was conducted in 2017 across a broad range of participants from the Georgian potato production sector. We present a model of the current potato seed exchange network for the most important agroecological regions. We integrated network analysis in a risk assessment for S. endobioticum spread in Georgia under 1) no intervention, 2) quarantine, 3) introduction of host plant resistance, and 4) combined quarantine and resistance deployment. Preliminary analyses suggest that under no intervention, risk of spread is high, while rapid and consistent quarantine can be effective. Methods presented here provide a general framework for future seed system risk assessments.